Influence of early withdrawals from private pension funds on inflation in Peru, 2020–2024 - Iparraguirre, Rosa María Quiñonez; Rojas, Percy Escalante (Edelweiss Applied Science and Technology, 2025)
This study aligns with Sustainable Development Goal No. 10, which aims to reduce economic and social inequalities. Its primary objective was to assess the impact of early withdrawals from private pension funds on inflation in Peru during 2020–2024. The research employed an applied, quantitative approach with a non-experimental, longitudinal, and causal correlational design. The sample consisted of official documentary records issued by the Superintendency of Banking, Insurance, and Pension Fund Administrators (SBS) and the Central Reserve Bank of Peru (BCRP). Documentary analysis was used as the technique, guided by a validated expert judgment. Data processing was conducted using SPSS v27 software. Results indicated a moderate positive correlation (r = 0.520) and a statistically significant influence (p = 0.035), demonstrating that early withdrawals significantly affected inflation in the country. The linear regression model showed that these withdrawals explained 22.4% of inflation variability. Additionally, they had a significant impact on core inflation (p = 0.022), but not on non-core inflation (p = 0.055). It is concluded that, although necessary, these measures generated sustained inflationary effects that threatened economic stability.